Implementation of the Sustainable Food Agricultural Land Protection (LP2B) Policy in West Pasaman Regency - Ahmad Fauzan; Nora Eka Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study analyzes the implementation of the Sustainable Food Agricultural Land Protection (LP2B) policy in West Pasaman Regency, identifies its inhibiting factors, and formulates local policy strengthening efforts. The research employed a descriptive qualitative approach using interviews, observation, and document study as data collection techniques. The analysis was based on Merilee S. Grindle's policy implementation theory, which emphasizes two main dimensions: policy content and implementation context. The findings indicate that the LP2B policy has a formal legal basis through West Pasaman Regional Regulation Number 5 of 2023 and involves several actors, including the Food Crops and Horticulture Office, Public Works and Spatial Planning Office, Regional Development Planning Agency, Land Office, village government, agricultural extension workers, farmer groups, and farmers. However, implementation remains suboptimal due to limited public understanding, uneven policy benefits, weak inter-agency coordination, fragmented land data, economic pressure, and inadequate irrigation infrastructure that still encourage land conversion. The novelty of this research lies in examining LP2B implementation in West Pasaman through an integrated analysis of policy content, institutional context, farmers' social risks, and rice production pressure from 2020 to 2024. The study concludes that LP2B should be strengthened through integrated land data, continuous socialization, cross-sector coordination forums, participatory supervision, and more tangible incentives for farmers.